1996
DOI: 10.1128/jcm.34.3.701-706.1996
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the vitek gram-positive susceptibility system's detection of vanB-encoded vancomycin resistance among enterococci

Abstract: Studies were conducted to identify factors contributing to the inability of the Vitek Gram-Positive Susceptibility system (GPS; bioMerieux, Vitek, Inc., Hazelwood, Mo.) to reliably detect vanB-mediated vancomycin resistance among enterococci. To some extent the accuracy of the GPS depended on a particular strain's level of resistance, as all isolates for which vancomycin MICs were >128 g/ml were readily detected but detection of resistance expressed by several strains for which MICs were <64 g/ml was sporadic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Differences were smaller but still apparent for vancomycin-resistant isolates. We noted that most of our enterococcal isolates grew relatively poorly in Mueller-Hinton broth, and several clinical isolates had to be excluded from the (12). Glycopeptide antibiotics act by binding of the peptidoglycan precursor lipid-linked N-acetylglucosamine-N-muramylpentapeptide at the D-alanine-D-alanine terminus (24,29).…”
mentioning
confidence: 99%
“…Differences were smaller but still apparent for vancomycin-resistant isolates. We noted that most of our enterococcal isolates grew relatively poorly in Mueller-Hinton broth, and several clinical isolates had to be excluded from the (12). Glycopeptide antibiotics act by binding of the peptidoglycan precursor lipid-linked N-acetylglucosamine-N-muramylpentapeptide at the D-alanine-D-alanine terminus (24,29).…”
mentioning
confidence: 99%
“…The reasons for these variations in reported susceptibilities are not clear, but the importance of different medium cation concentrations has been noted previously in reports evaluating antimicrobial susceptibilities of Pseudomonas aeruginosa to aminoglycosides and imipenem (8,19). It has been noted that susceptibility results for vancomycin may depend on the media used, the method employed, and the physicochemical characteristics of the drug, independent of the growth rate of the microorganism (15).…”
Section: Discussionmentioning
confidence: 99%
“…Accurate detection of resistant strains is important for microbiologists and clinicians in guiding optimal therapy for enterococcal infections and in implementing interventions to control and prevent nosocomial outbreaks (5). However, several studies have reported that some susceptibility testing methods, especially commercial automated systems and the commonly used disk diffusion test, are unable to detect resistance to key aminoglycosides and glycopeptides (2,7,9,23,30,34,36).…”
mentioning
confidence: 99%